2014
DOI: 10.3347/kjp.2014.52.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hydatid Cysts in Livestock Animals in Xinjiang, China

Abstract: Hydatid worms, hosted by humans and animals, impose serious human health risk and cause significant livestock production loss. To better understand the disease infection status in Xinjiang, China, we investigated the disease epidemics in 4 livestock animals, i.e., cattle, sheep (both sheep and goat), camels, and horses, slaughtered at the abattoirs in Urumqi, Yining, Tacheng, and Altay areas. The results showed that the animals were infected at different rates, in the order of sheep (9.8%), cattle (8.4%), came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 11 publications
5
23
0
1
Order By: Relevance
“…For goats, the rate of seropositivity between the different age groups was almost the same i.e., 24, 28 and 29% in 2-< 4 yrs old, 4-< 7 yrs old and over 7 yrs old respectively, these observations suggests that, transmission of CE can be occurred at any age of the animals with variable degree of infectivity and also agreed with the abattoir data that previously reported (Ongling et al, 2014). The slight differences in the total rate of seropositivity between both districts in general and between villages of each district could be due to sharing the same environmental conditions, grazing methods and human behaviour.…”
Section: Discussionsupporting
confidence: 80%
“…For goats, the rate of seropositivity between the different age groups was almost the same i.e., 24, 28 and 29% in 2-< 4 yrs old, 4-< 7 yrs old and over 7 yrs old respectively, these observations suggests that, transmission of CE can be occurred at any age of the animals with variable degree of infectivity and also agreed with the abattoir data that previously reported (Ongling et al, 2014). The slight differences in the total rate of seropositivity between both districts in general and between villages of each district could be due to sharing the same environmental conditions, grazing methods and human behaviour.…”
Section: Discussionsupporting
confidence: 80%
“…The prevalence of CE increase with the age, and usually animals are slaughtered at ages varies with countries and cultures, therefore, prevalence will typically be over-estimated if older animals are slaughtered and under estimated if younger animals are slaughtered (Barnes et al, 2012, Qingling et al, 2014and Al Kitani et al, 2015. Adult animals were more likely to have CE than younger ones.…”
Section: Discussionmentioning
confidence: 99%
“…Small ruminants (sheep and goats) three years or older were also found to be 1.6 times more at risk as compared to the younger groups. Additionally, an increase of cyst abundance has been reported in older age groups of farm animals (Al-Abbassy et al, 1980;Kamhawi et al, 2009Ibrahim, 2010Ibrahim et al, 2011;Andresiuka et al, 2013 andQingling et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Average infection rate of the sheep and cattle in Iran is 10 % (ranging 1-50 %) and 12 % (ranging 1-28 %) respectively (Dalimi et al 2006;Mousavi et al 2003). Qingling et al (2014) investigated the disease epidemics in livestock animals slaughtered at the abattoirs in China. The results showed that the animals were infected at different rates, in the order of sheep (9.8 %), cattle (8.4 %), camels (6.8 %), and horses (4.3 %).…”
Section: Discussionmentioning
confidence: 99%